Columbianetin protects from high-glycemic podocyte damage by regulating autophagy - Shi Lang; Song Zhi-xia; Zhang Ya-fei (Linchuang shenzangbing zazhi)
Objective To explore the protective effect of columbianetin（CBT）on the injury of podocytes induced by high glucose and its mechanism.Methods Immortalized murine foot cell line MPC-5 was cultured in vitro and the effects of CBT on injury and autophagy induced by high glucose were observed.Autophagy-related proteins were detected by Western blot.A fluorescent microscope was utilized for observing green fluorescent particles of GFP-LC3-Ⅱpodocyte after transfection.Results High glucose induced the injury of podocytes and decreased autophagy.CBT had a significant protective effect on the injury of podocytes induced by high glucose and could up-regulate autophagy.CBT up-regulated the expressions of TLR4 and p-JNK.siRNA TLR4 and inhibitor SP600125 blocked the protective effect of CBT.Conclusion CBT can induce autophagy in podocytes to protect podocytes from damage caused by high glucose.It is mediated by promoting TLR4/p-JNK signaling pathway.